Evidence for Conversion of Methanol to Formaldehyde in Nonhuman Primate Brain. (15th March 2016) - Zhai, Rongwei; Zheng, Na; Rizak, Joshua; Hu, Xintian
Abstract : Many studies have reported that methanol toxicity to primates is mainly associated with its metabolites, formaldehyde (FA) and formic acid. While methanol metabolism and toxicology have been best studied in peripheral organs, little study has focused on the brain and no study has reported experimental evidence that demonstrates transformation of methanol into FA in the primate brain. In this study, three rhesus macaques were given a single intracerebroventricular injection of methanol to investigate whether a metabolic process of methanol to FA occurs in nonhuman primate brain. Levels of FA in cerebrospinal fluid (CSF) were then assessed at different time points. A significant increase of FA levels was found at the 18th hour following a methanol injection. Moreover, the FA level returned to a normal physiological level at the 30th hour after the injection. These findings provide direct evidence that methanol is oxidized to FA in nonhuman primate brain and that a portion of the FA generated is released out of the brain cells. This study suggests that FA is produced from methanol metabolic processes in the nonhuman primate brain and that FA may play a significant role in methanol neurotoxicology.